Optimization of Rolling Process of Al-Plate Using Finite Element Method - Dr. Kamal S. Al-hamdani, Hawraa Sadaq (Mathematical Statistician and Engineering Applications, 2022)
A component's thickness is decreased to a specific thickness by exerting a desired pressure as it travels between two opposed rolls in the cold rolling process, an industrial shaping technique. This study looked at how aluminum plates' mechanical properties developed. In order to reach the appropriate thickness without annealing, the rolling process of aluminum plates was simulated, and the feasibility of substituting the hot rolling method of the aluminum plates manufactured in Ur Company/Iraq with a cold rolling process was studied. The residual stresses on the rolled plates were theoretically simulated by looking at several parameter windows. The effects of the process parameters on residual stresses and ultimate tensile strength were optimized and simulated using ABAQUS 310. (UTS). As a governing criterion for validation, the Von Mises method and an analogous plastic strain were applied (PEEQ). When studying high-temperature elastoplastic deformation of material during roll bite in a hot rolling process, the finite element method (FEM) is an effective tool. When the material composition of the workpiece varies, the roll bite stress field significantly alters. In this work, DEFORM-3D software is used to analyze roll bite deformation during the plate rolling process for a microalloyed steel grade.